Extraction of Foreign Body in Left Main Bronchus with Flexible Optical Bronchoscopy in Asymptomatic Needle Aspiration Patient: A Case Report - Antika, Puspa; Jito, Anggar (Jurnal Respirologi Indonesia, 2024)
Background: Foreign body aspiration is one of the most common respiratory and airway emergencies. The incidence is higher in children and obstruction occurrences are common. The late complications might be fatal when ignored. Bronchoscopy as a gold standard modality in diagnosing and treating this condition, now is widely available, and the emerging flexible optic bronchoscopy (FOB) is more commonly used.Case: A ten-year-old girl with a history of needle aspiration arrived at the ER with an asymptomatic condition. Further investigations reveal leucocytosis and a metal-needle-shaped foreign body found approximately in the left main bronchus via chest x-ray and CT scan. Bronchoscopy with FOB was performed under general anesthesia and LMA and successfully evacuated the needle although the pin had infiltrated the mucosal wall.Discussion: Asymptomatic foreign body aspiration is nearly at the same rate as symptomatic one. Management of difficulties and complications increases the longer the foreign body infiltrates the respiratory tract. Early diagnosis with chest x-ray and CT scan is necessary. Prompt and urgent evacuation of the foreign body is required. The use of FOB is associated with a higher success rate and lower complications. FOB is the best modality choice in this case.Conclusion: The foreign body in the respiratory tract may be asymptomatic. Early and proper diagnosis must be worked out as early management of asymptomatic foreign body aspiration. Early FOB can be used as a modality of choice in this case, preventing further damage to the respiratory tract.